Higher Technical Education:Some Considerations for Technical Universities - Deshmukh, S. G. (Journal of Engineering Education Transformations, 2010)
Since independence in 1947, technical education system in India has grown into a fairly large sized system, offering opportunities for education and training in a wide variety of trades and disciplines at certificate, diploma, degree, post graduate degree and doctoral levels in institute all over the country. In 1947, country had 38 degree level institutes with an intake capacity of 2500. Today we are having more than 1800 engineering institutes (not including IITS/NITs/) with an intake capacity of more than 600,000 students.